Epidemiology of knee injuries in Japanese collegiate rugby union players - Ryo Ogaki; Masahiro Takemura; Sho Takaki; Tatsuya Shimasaki; Takuo Furukawa (Japanese Society of Physical Fitness and Sports Medicine, 2017)
The purpose of this study was to describe the incidence, severity, mechanism, and intrinsic risk factors for knee injuries in Japanese collegiate rugby union players. Initially, 119 rugby union players from one university club were registered in this prospective cohort study. The occurrence of knee injuries was recorded by a team doctor and athletic trainers during the 2009-2012 playing seasons. The number of knee injuries recorded during these four seasons was 64. The incidence of knee injuries was significantly higher during matches (10.5 injuries/1000 player hours [ph]) than that during training (0.3 injuries/1000 ph). The most common match injury was the medial collateral ligament injury (4.4 injuries/1000 ph). The greatest severity and burden were observed for anterior cruciate ligament injuries (severity: 182.5 days, burden: 310.3 days/1000 ph). A majority of knee injuries were sustained during ruck/maul (26.6%) and step/cutting (20.3%). In addition, a history of injury (odds ratio [OR]: 3.3, 95% confidence interval [CI]: 1.3-8.4, p = 0.01) and rugby experience (<10 years, OR: 2.4, 95% CI: 1.1-5.7, p = 0.03) were considered as intrinsic risk factors for knee injuries. Although the total incidence of knee injuries in collegiate rugby union players was similar to that at a professional level, knee ligament injuries had a higher incidence and severity among college players. Injuries frequently occurred in ruck/maul for forward (FW) players and in step/cutting and being tackled position for back (BK) players. In this game, the risk of knee injury is high, and it varies for each field position, so preventive measures according to field position characteristics are necessary.